Selected lines from Tai Nguyen Cho Dao for drought tolerance and good grain quality in rice (Oryza saltiva.L) at Long An , VietNam - Nguyen, Lang thi; Anh, Khoa Bien; Huu, Linh Nguyen Van; Chi, Hieu Bui; Chi, Buu Bui (International Journal of Environment, Agriculture and Biotechnology, 2022)
Selected of Tai Nguyen Cho Dao (TNCD)rice varieties tolerant to drought, high-yielding and good quality is very essential demands has raised to provide poor farmers in coastlines conditions as lowland in Long An ,VietNam. The purpose of this experiment is to selected of 22 lines from TNCD rice varieties tolerant to drought on the basis of a combination of two methods by molecular markers and evaluated phenotype. Evaluating drought tolerance of 22 lines from TNCD on the basis in the field of drought conditions to select promising lines to meet for farmers applying into production. Methods: selection of drought tolerant alleles for landrace rice at Long An by SSR( simple sequence repeated) markers and evaluated phenotype. Results: Some high yielding and good drought tolerant lines as lines: (TNCD 01, TNCD 15 and TNCD 22), however, also many lines failed due to many reasons: expansion of growth day, high rate of unfilled grain, not good for grain quality. Three lines (TNCD01, TNCD15, TNCD22) good for three characters such as high yield, and tolerance with drought. Based on morphological and SSR marker the line TNCD 01, TNCD 22 was identified as good quality which was further confirmed through molecular characterization techniques using RM201, HATRI13D, RM328, RM316, RM 5353, RM3480 primers. Sequence of TNCD01; TNCD22 were submitted to GenBank with accession number MT992254 and MW917241 respectively. Tolerant lines from Tai Nguyen Cho Dao have high-yielding rice varieties. This is a opportunity to improve good landrace rice varieties for condition of selected drought landrace rice varieties in Long An ,Vietnam.